Allosteric Modulation of the Dopamine Receptor by Conformationally Constrained Type VI β-Turn Peptidomimetics of Pro-Leu-Gly-NH(2) - Vartak, Ashish (2007)
A peptidomimetic of Pro-Leu-Pro-NH(2), 7, possessing an indolizidinone type VI β-turn mimic was synthesized via improved high-yielding protocols for the preparation and Cbz-protection of α-allyl proline. Bicyclic peptidomimetic 7 and spirobicylic peptidomimetic 8 enhanced the binding of [(3)H]N-propylnorapomorphine to dopamine receptors indicating that a type VI β-turn is a possible bioactive conformation of the homochiral Pro-Leu-Pro-NH(2) and Pro-Pro-Pro-NH(2) analogues of Pro-Leu-Gly-NH(2) at the dopamine receptor allosteric regulatory site.